Prevalence of Frozen Shoulder among Patients Undergoing Cardiothoracic Surgery - Uddin, Md Jamal; Ahmed, MSA Mansur; Moniruzzaman, M; Rahman, Md Habibur; Uddin, Md Jalal; Siraj, Masoom (Ibrahim Cardiac Medical Journal, 2011)
Keywords: Frozen shoulder; cardiothoracic surgery; physiotherapy; treatment compliance Ibrahim Card Med J 2011; 1(1):14-16